2017
DOI: 10.21608/ejnf.2017.104119
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Selenomethionine Supplementation on Semen Quality, Fertility and Antioxidant Status of Cockerels

Abstract: he aim of this study was to determine the effect of different levels of Selenomethionine (Sel-Plex) (0.0, 0.15, 0.30 and 0.45 mg/kg diet) on semen quality, fertility and hatchability of local strain (Inshas) cockerels. Thirty six mature cockerels at 28 weeks of age were divided into four group {(G1 (0.0), G2 (0.15), G3 (0.30) and G4 (0.45)} mg/kg diet (9 cockerels each). All birds were reared under similar management and housing-condition throughout the experimental period. Results revealed that, the final liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…Testosterone hormone concentration illustrated in table (3) increased significantly (p≤ 0.05) in treatment group than control group in the second and third month of experiment. This result in agreement with Shamiah et al (2017) who illustrated that supplementation of diet with (0.30 mg/ kg diet) selenomethionine increased significantly testosterone concentration of Cockerels, but in contrast with Zhai et al (2016) who did not found significant effect of supplementation of diet with methionine on testosterone concentration of male broilers. This increase in concentration of testosterone revealed to that dietary supplementation with methionine improved growth and live body weight (LBW) and testosterone hormone was positively correlated with BW and the increase in growth and LBW may led to an increase in Testosterone concentration (Zhai et al, 2016;Ashton et al, 1995).…”
Section: Resultssupporting
confidence: 90%
“…Testosterone hormone concentration illustrated in table (3) increased significantly (p≤ 0.05) in treatment group than control group in the second and third month of experiment. This result in agreement with Shamiah et al (2017) who illustrated that supplementation of diet with (0.30 mg/ kg diet) selenomethionine increased significantly testosterone concentration of Cockerels, but in contrast with Zhai et al (2016) who did not found significant effect of supplementation of diet with methionine on testosterone concentration of male broilers. This increase in concentration of testosterone revealed to that dietary supplementation with methionine improved growth and live body weight (LBW) and testosterone hormone was positively correlated with BW and the increase in growth and LBW may led to an increase in Testosterone concentration (Zhai et al, 2016;Ashton et al, 1995).…”
Section: Resultssupporting
confidence: 90%